Wedelolactone, a natural coumestan with multiple pharmacological effects - Han, Shanshan; Li, Minghe; Yang, Longfei; Zhuang, Xinming (Frontiers in Pharmacology, 2026)
Natural products, especially those from medicinal plants, have been increasingly attractive to researchers. Wedelolactone (WL) is a natural coumestan that was first isolated from Wedelia Chinensis. The past decades have seen an increase in the pharmacological reports on this compound, which show that WL possesses anti-inflammatory, antiviral, antibacterial, antitumor and anti-osteoporosis activities, as well as protective effects on organ damages. This review integrates the recent progresses available on its pharmacological effects both in vitro and in vivo, and highlights its potential uses in multiple diseases.